ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESEMPATAN KERJA DI PROVINSI JAWA TENGAH TAHUN 1991-2020 - Ridwan Fajar Hidayat; Sadiah, Sudati Nur (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2021)
The increase in the number of workers in Central Java Province is one of the objectives of this study in analyzing the role of GRDP, the workforce, and the UMP in an effort to increase job opportunities during the period 1991-2020. This research uses multiple linear regression model with classical assumption test method and statistical test consisting of t test, f test, and coefficient of determination test (). The results of the study show a positive influence between GRDP and UMP growth with job opportunities. Furthermore, the labor force variable has a significant negative effect in increasing the level of employment opportunities. Another finding is that there is an influence between the variables of GRDP, labor force and UMP growth in increasing the level of employment in Central Java during the period 1991-2020. It is necessary to study other factors that can affect employment opportunities in Central Java, including interest rates, investment, number of companies, production value and so on